Improving Skills Development in the Informal Sector : Strategies for Sub-Saharan Africa - Adams, Arvil V.; Johansson de Silva, Sara; Razmara, Setareh (Washington, DC: World Bank, 2013)
This book looks at the experience of skills development in five African countries, Ghana, Kenya, Nigeria, Rwanda, and Tanzania, that together account for one-third of the nearly 900 million people living in Sub-Saharan Africa. The study examines: (a) the employment characteristics of the informal sector, (b) its size and impact on poverty, (c) the profile of education and training in the informal and formal sectors and the links with employment and earnings, and (d) the skills development strategies of those working in the informal sector. It draws on household survey data in the five countries as well as institutional analyses of the many programs offering opportunities for skills development. This book defines the nonfarm informal sector as follows: (i) the self-employed (that is, those working on their own and with additional workers), (ii) the contributing family members, and (iii) the wage workers in small and household enterprises. Chapter two discusses the background for this definition. The empirical analysis of the five country cases shows that the nonfarm informal sector is a significant part of the economic landscape in these countries. The study is well anchored in a larger literature on the informal sector, and its findings are linked to and consistent with this literature. Its findings are therefore expected to be relevant to many other countries in the region, as well as other regions such as South and East Asia. The book aims to provide insights and messages for a wide audience concerned with skills development. It raises issues relevant to government policy makers, the donor community, and those responsible for labor market institutions that provide information, regulate, and support the intermediation of labor demand and supply, as well as for public and private skills providers, employers, children and their parents, new labor market entrants, and of course those already working in the informal sector.